Handbook for the calculation of maximum flows and of the annual discharges on the small ungauged basins of Sahelian and dry tropical Africa - (:unkn) unknown (My University, 1996)
This handbook gathers the methods most frequently used in West Africa for calculation of maximum flows and of the annual discharges on the small basins of Sahelian and dry tropical Africa. It includes in a single handbook: 1) the compilation of all the existing data on the small basins of the zone. Is given in particular a file of 414 basins studied and listed, showing their hydrological characteristics, the observations of maximum flows and of the annual discharges ; 2) the revision and the updating of the principal methods of predetermination of the decennial flows ; 3) the presentation of the principal methods of determination of the decennial flows and of the annual discharges on small ungauged basins. Moreover, it presents the remote sensing and geographical Information systems possibilities of determining the hydrological characteristics of the small basins of this area.
Keywords: African Research